Consumer awareness towards electronic payment at the Klang Valley / Khairul Anuar Mohd Lamin - Mohd Lamin, Khairul Anuar (Faculty of Computer and Mathematical Sciences, 2004)
This study is carried out to determine the consumer awareness towards electronic payment in the Klang Valley. The target group is among consumers in the Klang Valley and focuses on people who had a past experience on using any of electronic payment services offered in Malaysia. This research will identify why, where, when, what, and how they use the electronic payment system. This study will also focus on people who had no experience on using any types of electronic payment services in Malaysia. This research will also identify why they do not use the electronic payment services. The purpose of this study is to give a real scenario about the awareness of people at Klang Valley towards electronic payment in Malaysia. This research will give some measurement about the frequency and consumer awareness and also highlight the knowledge level of Klang Valley peoples about electronic payment in Malaysia. From the finding shows that most of the respondent are aware about electronic payment that being offered. All of the respondents know about electronic payment before and like to pay their utility and telecommunication bills. Most of the respondents that have an experience on using electronic payment are satisfied and will recommend the electronic payment services to their friends. Most of them also do not find any difficulties on using electronic payment services. Most of them agreed that electronic payment services are easy to use. Most of them agreed that electronic payment is secured and saving their time compared to queuing at the counter. Respondents believes that electronic payment is beneficial to them but believe that electronic payment is slow in response time. They feel convenience on using electronic payment and agreed that electronic payment system in Malaysia needs more improvement.